2013
DOI: 10.3109/07357907.2012.756108
|View full text |Cite
|
Sign up to set email alerts
|

Elemene, One Ingredient of a Chinese Herb, Against Malignant Tumors: A Literature-based Meta-analysis

Abstract: We sought to evaluate the efficacy of elemene in cancer treatment. We searched the literature using several databases up to October 2011. Thirty-eight trials met inclusion criteria. The meta-analysis demonstrated that elemene plus chemotherapy was associated with a significant rise in the number of patients who reported improved tumor response, as well as a significant lower risk in patients with leucopenia as compared with chemotherapy alone. However, the pooled results failed to show favorable effects of ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Elemene has been shown to suppress signaling such as MAPK and PI3K/Akt/mTOR pathway involved in proliferation, induce cell death, up-regulate growth suppressors, deactivate invasion and metastasis, and attenuate angiogenesis (reviewed in [226]). Large variations in the quality and size of clinical trials reduces the reliability of the interpretation of the results, but a meta-analysis of 38 clinical trials showed an overall positive effect of elemene in combination with chemotherapy in lung cancer, hepatocarcinoma, metastatic brain cancer, and leukemia, but not in gastric carcinoma [235]. Another meta-analysis identified elemene injection as a safe and effective adjunctive treatment to platinum-based chemotherapy in patients with stage III/IV non-small cell lung cancer, where it showed enhanced efficacy and cellular immune function, as well as reduced the toxicity of chemotherapy.…”
Section: Elemenementioning
confidence: 99%
“…Elemene has been shown to suppress signaling such as MAPK and PI3K/Akt/mTOR pathway involved in proliferation, induce cell death, up-regulate growth suppressors, deactivate invasion and metastasis, and attenuate angiogenesis (reviewed in [226]). Large variations in the quality and size of clinical trials reduces the reliability of the interpretation of the results, but a meta-analysis of 38 clinical trials showed an overall positive effect of elemene in combination with chemotherapy in lung cancer, hepatocarcinoma, metastatic brain cancer, and leukemia, but not in gastric carcinoma [235]. Another meta-analysis identified elemene injection as a safe and effective adjunctive treatment to platinum-based chemotherapy in patients with stage III/IV non-small cell lung cancer, where it showed enhanced efficacy and cellular immune function, as well as reduced the toxicity of chemotherapy.…”
Section: Elemenementioning
confidence: 99%
“…Increasing attention has been paid to uncovering the anti-tumor potential and mechanisms of Chinese herbal medicine. Chinese herbs have been found to inhibit cell proliferation, angiogenesis and tumor metastasis, induce cell apoptosis and differentiation and regulate tumor-associated signaling pathways and the immune system ( 5 7 ), thus exhibiting anti-tumor potential in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…In China, it has been used as a therapeutic candidate for certain malignant tumors for several years (20). However, little is known about the underlying molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found that β-elemene could enhance tumor chemosensitivity or overcome drug resistance (17,18). In addition, β-elemene has been approved by the China Food and Drug Administration as a therapeutic drug in clinical practice where its efficacy has been exhibited when combined with first-line chemotherapy for malignant tumors (19,20). However, the mechanisms by which β-elemene is involved in tumor suppressing activities remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%